Harmonizing Policy and Needs: Encouraging Autonomy of State Islamic Religious Universities for Responsive Student Admission Policies in the Regions - Witri Puji Astuti (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper presents a policy analysis of the challenges faced by State Islamic Religious Colleges (PTKIN) in the regions due to the centralized national student admissions policy. The main argument put forward is that this one-size-fits-all approach has created a significant gap between centrally-made policies and real needs at the local level, thus hampering PTKIN's strategic role as agents of regional development. This paper adopts William N. Dunn's policy analysis framework, which begins with the identification of relevant policy issues. The main issue,